Enhancing Storyboarding for Viral Content: Closing the Research Gap in Interactive Storytelling on Digital Platforms - Paramita Hapsari, Paramita Hapsari (Akademi Komunikasi SAE Indonesia, 2025)
The rise of digital technology and social media platforms has transformed the creation of animated content, especially in storyboarding for viral projects. This study aims to identify and develop an effective storyboarding method tailored for viral content on digital platforms. The research method emphasizes audience interactivity, the integration of cutting-edge technology, and adaptation to global cultural differences. Using a qualitative approach, this research conducts content analysis and case studies of viral content across platforms like TikTok, Instagram, and YouTube. A key finding of this research is that storyboarding digital content must be flexible and sensitive to cultural variations. Additionally, it should accommodate diverse storylines that can evolve based on audience interactions. The study also reveals that technologies such as AI can enhance the relevance and efficiency of the storyboard creation process. Ultimately, it offers a practical guide for the creative industry to address the challenges associated with dynamic and cross-cultural content production.